Clash Characterization and Matrix Analysis Between Building Systems in BIM-Based Construction Projects - Nguyen, Minh Ngoc; Pham, Van Duong; Hoang, Van Bien; Tran, Ngoc Thang; Phonexaykham, Sendavanh (International Journal of Sustainable Construction Engineering and Technology, 2025)
Clashes in construction projects are among the key factors that reduce the efficiency of project delivery. In traditional 2D-based design, these clashes are difficult to detect because architectural, engineering, and construction (AEC) systems are not integrated within a unified platform. In contrast, Building Information Modeling (BIM) enables effective clash detection through specialized tools such as Revit and Navisworks. This study evaluates the effectiveness of clash detection by comparing the BIM process with conventional 2D drawings and identifies the main factors contributing to clashes in AEC models. Furthermore, it examines the interrelationships of clashes among different models within the BIM environment and develops a clash analysis diagram to facilitate their identification. Finally, the study proposes several solutions aimed at minimizing clashes during the design phase of construction projects when applying BIM.